The Process of Policy Formulation, Urban Planning and Design Which is Focused on The City of Tual - Matdoan, Usman A. (Ridwan Institute, 2025)
This study aims to see the relationship between the process of policy formulation, planning and urban design focused on Tual City. The results of the study show that the combination of the three indicators above shows a positive correlation where the city of Tual experiences a change in terms of urban and regional development for the better.